2020
DOI: 10.1108/ijssp-07-2020-0293
|View full text |Cite
|
Sign up to set email alerts
|

Does Karen wear a mask? The gendering of COVID-19 masking rhetoric

Abstract: PurposeThis paper asks how values and beliefs around gender influence social norms regarding masking. Specifically, the paper explores how the gendered meme “Karen” fits into social media discussions on support for and opposition to the wearing of masks to fight the spread of COVID-19.Design/methodology/approachThe authors analyze tweets containing the hashtags #Masks4All and #NoMasks over a three-week period, using adjacent hashtag analysis to determine the terms most associated with Karen in the pro and anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 8 publications
(7 reference statements)
2
37
0
1
Order By: Relevance
“…While providing a window on the relative interaction frequencies of pro- and anti-mask tweeters with robust data, this narrow focus certainly could not capture all interactions or lack of interactions between the tweeters, and may have limited the informativeness of our results, especially in the analysis of the echo chamber effect. Lastly, previous studies found that COVID-19 mask rhetoric in social media is gendered [ 86 ], that there is a gender difference in the likelihood of mask-wearing in public [ 69 , 76 ], and that male leaders who value a macho image tend to eschew masks because they perceive mask wearing as emasculating [ 87 ]. One of the pro-mask hashtags in our data, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…While providing a window on the relative interaction frequencies of pro- and anti-mask tweeters with robust data, this narrow focus certainly could not capture all interactions or lack of interactions between the tweeters, and may have limited the informativeness of our results, especially in the analysis of the echo chamber effect. Lastly, previous studies found that COVID-19 mask rhetoric in social media is gendered [ 86 ], that there is a gender difference in the likelihood of mask-wearing in public [ 69 , 76 ], and that male leaders who value a macho image tend to eschew masks because they perceive mask wearing as emasculating [ 87 ]. One of the pro-mask hashtags in our data, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative research with college students and their families has shown that women and mothers played a key role in managing the risks of COVID-19, and that those roles led women and mothers to take more steps to manage risks (Umamaheswar and Janani 2020). Women, for example, were more likely than men to report wearing masks and taking other steps to keep their families' safe (Bhasin et al 2020;Cassino and Besen-Cassino 2020;Haischer et al 2020;Kramer 2020;Palmer and Peterson 2020). At the same time, research has also shown that women were less likely than men to report intentions to receive the COVID-19 vaccine (Callaghan et al 2021;Funk and Tyson 2020).…”
Section: Anticipating Oppositionmentioning
confidence: 99%
“…Numerous studies have analyzed the role played by masks during the COVID-19 pandemic [26]: masks have been associated with a reduction in the infection rate among health care workers in a large hospital network [7], mask mandates have helped reduce the number of cases in the United States and in Germany [8–10], and simulations have shown that wearing a mask can protect against droplet infection by preventing the spread of viral particles [1116]. Despite this evidence, there has been strong resistance against mask-wearing [1720], and the states of Texas and Mississippi recently lifted their mask mandates even though they have some of the lowest vaccination rates in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have analyzed the role played by masks during the COVID-19 pandemic [2][3][4][5][6]: masks have been associated with a reduction in the infection rate among health care workers in a large hospital network [7], mask mandates have helped reduce the number of cases in the United States and in Germany [8][9][10], and simulations have shown that wearing a mask can protect against droplet infection by preventing the spread of viral particles [11][12][13][14][15][16]. Despite this evidence, there has been strong resistance against mask-wearing, begging the question of the role played by attitudes towards masks in determining COVID-19 outcomes, and whether mask mandates could lead to an increase in adherence [17][18][19]. Investigating these questions is a key component of an ongoing effort to determine how to design, implement and sustain the adoption of non-pharmaceutical interventions (NPIs) to curb the spread of the COVID-19 pandemic [20][21][22][23][24][25].…”
mentioning
confidence: 99%
See 1 more Smart Citation